Impact of unsuspected subsegmental pulmonary embolism in ICU patients - Koch, Christian; Schramm, R.; Roller, F.C.; Hecker, Andreas; Henrich, M.; Schneck, E.; Krombach, G.; Weigand, Markus A.; Lichtenstern, Christoph (Der Anaesthesist, 2016)
Critically ill patients in intensive-care units are at high risk for pulmonary embolism (PE). As a result of modern multi-detector computed tomographic angiography (MDCT) increased visualization of peripheral pulmonary arteries, isolated subsegmental pulmonary embolisms (ISSPE) are increasingly being detected.